Knockdown of Ift88 in fibroblasts causes extracellular matrix remodeling and decreases conduction velocity in cardiomyocyte monolayers - Ernault, Auriane C.; Kawasaki, Makiri; Fabrizi, Benedetta; Montañés-Agudo, Pablo; Amersfoorth, Shirley C. M.; Al-Shama, Rushd F. M.; Coronel, Ruben; De Groot, Joris R. (Frontiers in Physiology, 2022)
Background: Atrial fibrosis plays an important role in the development and persistence of atrial fibrillation by promoting reentry. Primary cilia have been identified as a regulator of fibroblasts (FB) activation and extracellular matrix (ECM) deposition. We hypothesized that selective reduction of primary cilia causes increased fibrosis and facilitates reentry. Aim: The aim of this study was to disrupt the formation of primary cilia in FB and examine its consequences on ECM and conduction in a co-culture system of cardiomyocytes (CM) and FB. Materials: Using short interfering RNA (siRNA), we removed primary cilia in neonatal rat ventricular FB by reducing the expression of Ift88 gene required for ciliary assembly. We co-cultured neonatal rat ventricular cardiomyocytes (CM) with FB previously transfected with Ift88 siRNA (siIft88) or negative control siRNA (siNC) for 48 hours. We examined the consequences of ciliated fibroblasts reduction on conduction and tissue remodeling by performing electrical mapping, microelectrode, and gene expression measurements. Results: Transfection of FB with siIft88 resulted in a significant 60% and 30% reduction of relative Ift88 expression in FB and CM-FB co-cultures, respectively, compared to siNC. Knockdown of Ift88 significantly increased the expression of ECM genes Fn1, Col1a1 and Ctgf by 38%, 30% and 18%, respectively, in comparison to transfection with siNC. Conduction velocity (CV) was significantly decreased in the siIft88 group in comparison to siNC (11.12+/-4.27 cm/s (n=10) vs 17.00+/-6.20 (n=10) respectively, P<.05). The fraction of sites with interelectrode activation block was larger in the siIft88 group than in the siNC group (6.59x10^2+/-8.01x10^2 vs 1.18x10^2+/-3.72x10^2 respectively, P<.05). We documented spontaneous reentrant arrhythmias in two cultures in the siIft88 group and in none of the siNC group. Action potentials were not significantly different between siNC and siIft88 groups. Conclusion: Disruption of cilia formation by siIft88 causes ECM remodeling and conduction abnormalities. Prevention of cilia loss could be a target for prevention of arrhythmias.